ANALYSIS OF FACTORS INFLUENCING THE USE OF SUPPLEMENTS OR VITAMINS IN STUDENTS OF ISLAMIC STATE UNIVERSITY OF NORTH SUMATERA - Situmorang, Irsyad Baihaqi; Angkat, Chairunissa T. D. E.; Nasution, Mutiara; Pohan, Dhea Afriza; Wahyudi, Wahyudi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
The use of supplements and vitamins has become part of the modern lifestyle, including among university students, as an effort to maintain health, increase endurance, and complement daily nutritional needs. This study aims to investigate the various internal and external factors that influence the use of supplements and vitamins by students at the State Islamic University of North Sumatra (UINSU). The method used in this study is a quantitative approach with a cross-sectional research design. Samples were taken by simple random sampling method from active students, taking into account predetermined inclusion and exclusion criteria, and the sample size was determined based on the Slovin formula. Data were collected using a questionnaire covering aspects of knowledge about nutrition, eating habits, physical activity, health conditions, peer influence, and exposure to the media. Data were analyzed descriptively and analytically using the chi-square (χ²) test with a significance level of p < 0.05. The results of this study indicate that the most influential factor in the use of supplements and vitamins is the appearance factor, in the statistical test results obtained P Value 0.012 or (<0.05) which means that the appearance factor shows a significant relationship to the use of supplements and vitamins. Conclusion: the most influential factor in the use of supplements and vitamins is the appearance factor, while the other two factors, namely the knowledge factor, there is no relationship between knowledge and the frequency of taking vitamins, and the exposure factor is also not related to the frequency of taking vitamins.